2014
DOI: 10.1159/000363057
|View full text |Cite
|
Sign up to set email alerts
|

Male-Specific Use of the Purr in the Ring-Tailed Lemur <b><i>(Lemur catta)</i></b>

Abstract: In mammals, purring has been described in mostly affiliative contexts. In the ring-tailed lemur (Lemur catta), both males and females purr, but only males were observed purring in agonistic contexts. In order to determine whether male ring-tailed lemurs purr as aggressive displays during intrasexual agonistic encounters, 480 h of focal data were collected on 25 adult males from Beza Mahafaly Special Reserve, Madagascar, from March to July 2010. The male purring rate increased during periods of male-male agonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…Previous support for this hypothesis had been found in vervet monkeys (Chlorocebus pygerythrus) and tufted capuchin monkeys (Cebus apella) [Cheney and Seyfarth, 1985;van Schaik and van Noordwijk, 1989]. For some L. catta vocalizations, the vocalization rate is known to be correlated with individual male dominance rank [Bolt, 2013c[Bolt, , 2014, but alarm calls do not fit this trend. In contrast to primate species such as C. pygerythrus and C. apella , in which dominant males are thought to derive fitness benefits from calling at increased rates [Cheney and Seyfarth, 1985;van Schaik and van Noordwijk, 1989], dominant male L. catta may not alarm-call at higher rates because they may not receive any benefits from doing so.…”
Section: Discussionmentioning
confidence: 98%
“…Previous support for this hypothesis had been found in vervet monkeys (Chlorocebus pygerythrus) and tufted capuchin monkeys (Cebus apella) [Cheney and Seyfarth, 1985;van Schaik and van Noordwijk, 1989]. For some L. catta vocalizations, the vocalization rate is known to be correlated with individual male dominance rank [Bolt, 2013c[Bolt, , 2014, but alarm calls do not fit this trend. In contrast to primate species such as C. pygerythrus and C. apella , in which dominant males are thought to derive fitness benefits from calling at increased rates [Cheney and Seyfarth, 1985;van Schaik and van Noordwijk, 1989], dominant male L. catta may not alarm-call at higher rates because they may not receive any benefits from doing so.…”
Section: Discussionmentioning
confidence: 98%
“…Although one‐zero sampling has received criticism (e.g., Altmann, ), this sampling method has also been empirically shown to be an effective technique for collecting data on primate behavioural rates (Leger, ; Rhine & Linville, ; Sarfaty, Margulis, & Atsalis, ; Suen & Ary, ), and has been used in other studies on primate vocalisations (e.g., Bolt, ,c, ; Bolt et al., ; Clarke, Reichard, & Zuberbühler, ; Suzuki & Sugiura, ). We used one‐zero sampling because Bernstein () recommended that one‐zero scoring should be used when behavioural acts are clustered and the bout, rather than each act, is of interest.…”
Section: Methodsmentioning
confidence: 99%
“…Behaviour classified as agonistic could be high arousal (e.g., bite/jump away, chase/flee, stalk/cower or attack/withdraw) or low arousal (e.g., displacement/be displaced, or stare/look away) (Gould, ; Parga, , ; Pereira & Kappeler, ). We determined individual male dominance scores from these data following methods described in detail by Bolt (,c, ), using dominance index calculations (Zumpe & Michael, ), which take all aggressive and submissive interactions in each group into account before assigning an individual dominance percentage to each group member based on the relative number of agonistic wins. High dominance percentages correlate with high dominance levels, while low dominance percentages correlate with low dominance levels.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In primates, a group cohesion function has often been ascribed to close calls (e.g., Palombit, 1992), but studies have found evidence supporting additional functions such as reduction of competition within foraging patches (Boinski & Campbell, 1996), facilitation of affiliative social interactions among group members (Cheney, Seyfarth, & Silk, 1995), and mediation of aggressive interactions among males (Bolt, 2014). Meerkats (Suricata suricatta) utilize loud calls as part of a functionally referential alarm call system and to coordinate wholegroup behaviour (Manser, 1998).…”
Section: Contact and Group Cohesionmentioning
confidence: 99%